(untitled) (Physical Culture and Sport: Scientific Perspective, 2024)
Modern training of athletes in aerobic gymnastics requires an integrated approach, which includes not only the development of strength and endurance, but also the improvement of coordination, flexibility and special techniques for performing elements. With the development of this young sport, the requirements for gymnasts have become much higher, and training has become much more complicated. Modern coaches make programs taking into account the physical capabilities and level of training of each athlete, which increases efficiency and reduces the risk of injury. In aerobic gymnastics, much attention is paid to exercises to develop body balance and accuracy of movements, cultivate a sense of rhythm and synchronize the performance of the composition with musical accompaniment. The use of special simulators and stabilization exercises help athletes improve body control, which is necessary when performing complex combinations, but they do not affect the development of rhythm and coherence of movements with music. The article considers the effectiveness of the program of development of coordination abilities of athletes of the basic training group using music games. When developing the program, the choice of music games was appropriate in relation to the development of types of coordination abilities (temporo-spatial orientation, rhythm, evaluation and regulation of movement parameters, maintaining balance, muscle feeling). The implementation of this program showed a positive effect on the development of coordination abilities and showed a likely improvement in the performance of the tests: rhythmic tapping with hands (p < 0.05), the flamingo balance test 1 minute (p < 0.10), the Kopylov test (p < 0.05), jumping to the markup (p < 0.05). So, music games help to improve balance, synchronization of movements, rhythm and reaction speed, which are key to success in aerobic gymnastics.